Multivariate analyses to evaluate the contamination, ecological risk, and source apportionment of heavy metals in the surface sediments of Xiang-Shan wetland, Taiwan - Salah-Tantawy, Ahmed; Chang, Ching-Sung Gavin; Young, Shuh-Sen; Lee, Ching-Fu (Frontiers in Public Health, 2025)
Nowadays, heavy metal (HM) contamination and their ecological risk in coastal sediments are global issues. This research provides insight into the heavy metals’ contamination, source apportionment, and potential ecological risks in the surface sediments of the Xiang-Shan wetland in Taiwan, which is undergoing rapid economic development, mainly by the semiconductor industries. The levels of twelve metals and total organic matter (TOM) were measured in 44 samples of surface sediment during the spring and winter seasons of 2022. Subsequently, the single and comprehensive pollution indices were assessed. The findings showed that the average of HM contents exhibited a descending sequence of Al > Fe > Mn > Zn > Co > Ga > Cr > Cu > In > Ni > Pb = Cd during both seasons. The Ef, Igeo, and PI showed that the majority of sediment samples were uncontaminated to heavily contaminated by Fe, Al, Zn, Cu, Mn, Cr, Ni, Co and Ga, and extremely contaminated by In. Moreover, PLI and mCdeg unveiled that the surface sediments of DJ, OB, and KY stations were strongly or extremely polluted. PERI revealed that the sediment shows minimal to moderate ecological risk. The findings of multivariate analyses suggested that Fe, Al, Cu, Zn, and Ni derived from natural sources, while Ga, In, Co, Cr, and Mn originated from both anthropogenic and natural origins. Hence, it is critical that HM contamination, particularly Co, In, and Ga, be continuously monitored in the study area. Our data provide significant insights for more effective prevention and evaluation of HM contamination in the aquatic-sedimentary ecosystems of Taiwan.